Factors affecting early psychiatric intervention for patients with first‐episode psychosis in Japan. Issue 3 (22nd July 2012) - Hagi, Noriko; Takamura, Mitsuyuki; Yokoyama, Kazuhito
Abstract: Aim: The present study aimed to clarify the factors affecting early psychiatric intervention for patients with first‐episode psychosis in Japan. Methods: A postal questionnaire survey was conducted in 346 members of the Association of Family of Psychosis Patients, in Mie, Japan. Results: The questionnaire was completed by 138 respondents. The mean interval between a suspected first episode of psychosis and the first visit to a medical institution was 18.4 months (SD: 40.0, range: 0–336 months). Forty‐five respondents consulted a family member first and required a mean duration of 9.8 months (SD: 11.2) before their first visit; this was significantly shorter than those who did not. Eighteen respondents consulted their class teacher at school first and required a mean duration of 40.2 months (SD: 63.0) before their first visit; this was significantly longer ( P < 0.05) than those who did not. When loss of sleep or appetite was present, the mean duration before their first visit was 9.3 months (SD: 12.1), which was significantly shorter ( P < 0.05) than the time required by those who did not. Logistic regression analysis using the first episode‐first visit interval as an independent variable, and independent variables such as age, gender of the patient and family member, and loss of sleep, revealed that variables relating to the respondent's notion about the psychosis were mitigating factors (e.g. 'prejudice‐causing' and 'nothing to do with me'). Conclusion: Prejudice towards psychosis and poor awareness about mental illnesses are two factors that may affect early psychiatric intervention.